Pengembangan E-Modul Interaktif Dengan Menggunakan Model Pbl Dalam Pembelajaran IPA Materi Organ Pencernaan Pada Hewan dan Manusia di SD N 0601 Paringgonan - Parapat, Khoiriah Marta; Rahmadani, Annisa; Ardiyani, Fenika; M, Maswariyah; Ulkhaira, Nabila; Ramadhani, Rizki (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Electronic modules or e-modules, are defined as learning media using computers that display text, images, graphics, audio, animation and video in the learning process. The aim of this research is to find out how to develop an interactive e-module using the PBL model in science learning regarding Digestive Organs in Animals and Humans at SD N 0601 Paringgonan. The method used in this research is to use the ADDIE model, namely Analysis, Design, Development, Implementation and Evaluation. The results of this research state that this PBL-based interactive e-module has been successfully developed. This PBL-based interactive e-module was declared suitable for use in learning according to the validation results of material experts, media experts and language experts with an average of 885, 895 and 91.75% respectively. The implementation results stated that student learning outcomes increased from series 1 to the next series. Students' responses to the use of PBL-based interactive e-modules in the teaching and learning process were classified in the very good category with an average of 90.86%.